2020
DOI: 10.1007/s10664-020-09854-3
|View full text |Cite|
|
Sign up to set email alerts
|

Wait for it: identifying “On-Hold” self-admitted technical debt

Abstract: Self-admitted technical debt refers to situations where a software developer knows that their current implementation is not optimal and indicates this using a source code comment. In this work, we hypothesize that it is possible to develop automated techniques to understand a subset of these comments in more detail, and to propose tool support that can help developers manage self-admitted technical debt more effectively. Based on a qualitative study of 333 comments indicating self-admitted technical debt, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
(56 reference statements)
0
29
0
Order By: Relevance
“…Classifier preparation. Previous studies [26,27,49] reported that classifiers trained by combining N-gram IDF and auto-sklearn machine learning tend to outperform classifiers that are trained with single word features. Heeding their advice, we train our classifiers using auto-sklearn [12], which automatically determines effective machine learning pipelines for classification.…”
Section: Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Classifier preparation. Previous studies [26,27,49] reported that classifiers trained by combining N-gram IDF and auto-sklearn machine learning tend to outperform classifiers that are trained with single word features. Heeding their advice, we train our classifiers using auto-sklearn [12], which automatically determines effective machine learning pipelines for classification.…”
Section: Approachmentioning
confidence: 99%
“…An analysis of coded SATD comments revealed that bug report links usually appear in comments. Thus, for all SATD comments, we replace hyperlinks with abstracturl by using the regular expression similar to the previous study [27]: h t t p s ? : \ / \ / (www\ . )…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al [13] used the text-mining based methods to predict whether a comment contains SATD or not. Rungroj et al [21] first introduced the concept of "on-hold" SATD and proposed a tool [20] to identify and remove the "on-hold" SATD automatically. Even if obsolete TODOs and "on-hold" SATD are similar, there are several differences between our work and theirs: (i) According to their definition in [21], the "on-hold" SATD contains a specific condition to be triggered, while the obsolete TODOs in our study do not have such constraint.…”
Section: Related Work 81 Todo Comments In Se Researchmentioning
confidence: 99%